Transformasi Pembelajaran Bahasa Indonesia di Sekolah Dasar melalui Deep Learning Berbasis Delapan Dimensi - Yoma Hatima (Jurnal Pendidikan, Kepelatihan, Olahraga, dan Kesehatan, 2025)
Indonesian language learning in elementary schools (SD) plays a strategic role in developing students' literacy, communication skills, and character. In the context of 21st-century education, the eight dimensions of Deep Learning faith and devotion to God Almighty, citizenship, critical reasoning, creativity, collaboration, independence, health, and communication serve as important guidelines in building students' holistic competencies. The Deep Learning approach emphasizes deep engagement, active learning, and character development through meaningful activities. This article presents a systematic literature review (SLR) related to the integration of the eight dimensions of Deep Learning in Indonesian language learning in elementary schools. The study was conducted by reviewing national and international publications from the Scopus, Google Scholar, and Sinta databases published between 2015 and 2025. The results show that implementing learning strategies that integrate these eight dimensions improves students' learning motivation, literacy, creativity, and communication. Project-based activities, collaboration, and the use of interactive digital media have been shown to support the strengthening of students' character and independence. These findings confirm that transforming Indonesian language learning through Deep Learning, focusing on these eight dimensions, not only improves academic competence but also shapes students with faith, character, health, and readiness to collaborate effectively. This study recommends the development of an adaptive learning model based on these eight Deep Learning dimensions for optimal implementation in elementary schools.